2006
DOI: 10.1681/asn.2006050495
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Coxsackie B4 Virus in Hyper-IgA Mice

Abstract: For clarification of the pathogenetic role of viral infection in chronic glomerulonephritis, the renal effects of Coxsackie B4 virus (CB4) were examined in hyper-IgA (HIGA) mice. In experiment 1, HIGA mice (n ‫؍‬ 75) were inoculated intravenously with live CB4 and inactivated CB4 once a month from 1 to 12 mo of age. In experiment 2, HIGA mice (n ‫؍‬ 45) were inoculated intravenously with live CB4 and inactivated CB4 once at 6 wk of age. In experiment 3, 60 mice were inoculated intravenously with carbon and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…*P Ͻ 0.05; **P Ͻ 0.01. 29 reported that viral infection can provoke renal injury also in murine IgAN. For assessment of potential influence of exogenous pathogens on the disease progression, the IgAN-prone ddY mice were maintained separately under the conventional and SPF conditions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ 0.05; **P Ͻ 0.01. 29 reported that viral infection can provoke renal injury also in murine IgAN. For assessment of potential influence of exogenous pathogens on the disease progression, the IgAN-prone ddY mice were maintained separately under the conventional and SPF conditions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoperoxidase staining for α-SMA, PCNA, VEGF, Ang-1, and CD31 was evaluated using the methods previously described by Kawasaki et al [18,19]. Primary antibodies included mouse anti-human α-SMA (1A4; Dako, Glostrup, Denmark), mouse anti-human PCNA (19A2; Coulter, Hialeah, Fla., USA), goat anti-mouse VEGF (RM0008-6572; NOV) monoclonal antibodies, rabbit anti-mouse Ang-1 (Anti-AUGPT1; LSB), and rabbit anti-mouse CD31 (ER-MP12; BMA) polyclonal antibodies were used for IHM.…”
Section: Methodsmentioning
confidence: 99%
“…In many of these systems, genetic proclivity for altered systemic immunity is recognized and likely explains the predominance of IgAN [49][50][51]. However, in some instances, the known parameters of the immune response would not necessarily predict predilection for a strong IgA response or alterations in immunoregulation; nonetheless, strong serum IgA responses and IgA predominance or co-dominance in a subsequent glomerulonephritis is observed [68][69][70][71][72]. The antigens in these systems are bacterial or viral pathogens that might invoke innate immunity, which modulates the adaptive antibody response through mechanisms that are currently being elucidated (see 'T Cell Regulation and Cytokine Polarity' , below).…”
Section: Generation Of Iga By Extramucosal (Systemic) Immunizationmentioning
confidence: 99%
“…Indeed, co-stimulation with 'superantigen' , vaccination of selected strains of rodents predisposed towards an immune response favoring IgA production and/or Th2 cytokine profiles, or immunomodulation by innate responses can also lead to IgAN [33,36,[49][50][51][68][69][70][71][72]. In addition, very intense cognate responses can drive immune responses with specificity for elements that are not a component of the intense stimulus, which is especially true for simpler antigens, those that resemble commensals or pathogens, or those that are prevalent in the environment in which the host survives.…”
Section: Polyclonal Activation and Dysregulated Ig Productionmentioning
confidence: 99%
See 1 more Smart Citation